Contextual and experiential aspects of the psychedelic experience predicting improvement in subjective wellbeing: results from a Norwegian internet convenience sample - Paula Aarseth Tunstad; Tor-Morten Kvam; Tor-Morten Kvam; Malin V. Uthaug; Malin V. Uthaug; Lowan H. Stewart; Kristoffer A. A. Andersen; Cato Grønnerød (Frontiers in Pharmacology)
BackgroundInterest in the therapeutic effects of classical psychedelics has risen recently. However, little epidemiological knowledge exists about the use of classical psychedelics in Scandinavian countries. Additionally, there is a limited understanding of what factors drive self-reported improvement in wellbeing. The aim of this study was to investigate the relationship between the use of classical psychedelics and outcomes related to subjective wellbeing in an adult, Norwegian-speaking sample. We examined how contextual and phenomenological variables were associated with self-reported subjective wellbeing.MethodsUsing an anonymous internet survey, we recruited Norwegian speaking subjects who have had a memorable experience after taking a classic psychedelic substance. Data are presented by using descriptive statistics about the sample and two hierarchical regression analyses. The first regression analysis examined contextual variables, and the second examined variables related to acute phenomena during the experience.ResultsThe survey showed that 85% of the sample reported a small to large positive change in subjective wellbeing after their experience with classical psychedelics. Integration, ego dissolution, and emotional breakthrough had a clear, positive predictive effect on the participants’ self-reported subjective wellbeing. Variables with lower but significant effects were the degree of challenging experiences, settings associated with nature or ceremony, and a therapeutic or seeking intention.ConclusionThe use of classical psychedelics leads to an increase in subjective wellbeing for the majority of the participants. This relationship seems dependent upon various experiential aspects of acute subjective drug effects. These findings should be viewed as hypothesis-generating rather than confirmatory due to the study’s limitations.